Mothers’ Knowledge, Attitude and Practice regarding Prevention of Diarrhea among Children: An Empirical Investigation - Manjura Khatun; Afroza Sharmin; Ishrat Jahan Bithi (Randwick International of Social Science Journal, 2021)
The descriptive type of cross-sectional study was carried out to find out the mothers’ knowledge, attitude and practice regarding the prevention of diarrhea among children at Kamarpara Slum Area, Dhaka. In this study, 110 mothers were interviewed. It was found from the current study that the age distribution of the study population, out of total 110 respondents, 46.4% of the respondents belongs to the age group 20-29 years. The study showed that only 47.3% of women have completed primary education, majority of the respondents (69.1%) lived in kacha house, above half of the respondents (62.7%) agreed that diarrhea means passage of loose or watery stools >3 times in 24 hours, majority of the respondents (46.4%) got information from TV, most of the respondent’s children (88.2%) suffered from diarrhea, most of the respondents (70.9%) had given EBF to their child during diarrhea where as 29.1% didn’t practice EBF during diarrhea. Most of the respondents (79.1%) were aware about the causes of diarrhea,74.5% respondents had knowledge on danger signs of diarrhea, 25.5% didn’t know about danger signs of diarrhea.85.5% respondents said that diarrhea can be prevented by drinking clean water.75.5% respondents said that hand washing prevents diarrhea,46.4% respondents drinks water from Tube-well, majority of the respondents (55.5%) used sanitary latrine, 36.4% used non-sanitary latrine,20% respondents didn’t wash their hands properly,33.6% washed their hands with plain water,58.2% respondents placing child’s stool in toilet, 87.3% respondents gave ORS to their child during diarrhea, more than half of the respondents didn’t know the preservation time of ORS, only 22.7% said the preservation time of ORSis10-12 hours. 81.8% of the respondents cut nail timely. In conclusion the knowledge of mothers on diarrhea was poor there is a need for extensive educational interventions of mothers about childhood diarrhea to reduce the suffering from dehydration of children.